Bacterial sterilization by a dielectric barrier discharge (DBD) in air - Kostov, K. G. [UNESP]; Rocha, V. [UNESP]; Koga-Ito, C. Y. [UNESP]; Matos, B. M. [UNESP]; Algatti, M. A. [UNESP]; Honda, Roberto Yzumi [UNESP]; Kayama, M. E. [UNESP]; Mota, Rogério Pinto [UNESP] (Elsevier B.V. Sa, 2010)
Cold atmospheric plasma treatment of microorganisms and living tissues has become a popular topic in modern plasma physics and in medical science. The plasma is capable of bacterial inactivation and noninflammatory tissue modification, which makes it an attractive tool for treatment of skin diseases, open injuries and dental caries. Because of their enhanced plasma chemistry, Dielectric Barrier Discharges (DBDs) have been widely investigated for some emerging applications such as biological and chemical decontamination of media at ambient conditions. Despite the high breakdown voltage in air at atmospheric pressure, the average current of DBD discharges is low. Therefore, a DBD can be applied in direct contact with biological objects without causing any damage. In this work a 60 Hz DBD reactor, which generates cold atmospheric plasma inside Petri dishes with bacterial culture, is investigated. Samples of Staphylococcus aureus, a Gram-positive bacterium and Escherichia coil a Gram-negative bacterium were selected for this study. The bacterial suspensions were evenly spread on agar media planted in Petri dishes. The reactor electrodes were placed outside the Petri dish, thus eliminating the risk of samples microbial contamination. The covered Petri dish with agar medium in it serves as dielectric barrier during the treatment. The plasma processing was conducted at same discharge power (similar to 1.0 W) with different exposure time. Sterilization of E. coil and S. aureus was achieved for less than 20 min. Plasma induced structural damages of bacteria were investigated by Scanning Electron Microscopy. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Atmospheric plasma; Dielectric barrier discharge; Plasma sterilization; E. coli; S. aureus